A Bigger Piece of the Pie? : State Corrections Spending and the Politics of Social Order - Stucky, Thomas D. (Journal of research in crime and delinquency, 2007)
The dramatic increase in American state prison populations during the past three decades has sparked considerable research interest. Empirical research has most often examined changes in prison admissions or populations, but few studies have considered shifts in state corrections budgets. This study examines variation in annual, state-level corrections expenditures as a proportion of state expenditures from 1980 to 1998, drawing together existing theoretical arguments about criminal punishment under a common rubric that focuses on state responsibility for the maintenance of social order and the need for state officials to maintain office through popular election. From this view, partisan politics, economic and racial threats, citizen preferences, fiscal considerations. policy priorities, and crime are important explanations of corrections spending because they affect strategies for maintaining social order, garnering votes, and maintaining political office. Findings generally support this perspective. Partisan politics, racial threats, state economic prosperity, and budgetary priorities all play a role in determining state corrections expenditures. [ABSTRACT FROM AUTHOR]